Clinical and economic evaluation of tapentadol extended release and oxycodone/naloxone extended release in comparison with controlled release oxycodone in musculoskeletal pain. (June 2014) - Coluzzi, Flaminia; Ruggeri, Matteo
Abstract Objective: Chronic pain is a leading cause of disability and represents a relevant societal burden. Opioids are widely used for managing chronic non-cancer pain; however, the high incidence of side effects is often the main reason for discontinuation. Two formulations have recently been studied to improve the tolerability of opioids (tapentadol extended release [ER] and oxycodone/naloxone ER), but a direct comparison between these drugs is not available in the literature. The comparative cost effectiveness of these two drugs has not previously been assessed. The objective of this meta-analysis is a clinical and economic evaluation of tapentadol ER and oxycodone/naloxone ER for the treatment of musculoskeletal pain, by indirect comparison with controlled release (CR) oxycodone. Methods: A structured literature review was conducted to identify published data for the health-economic model. The authors performed a meta-analysis on three selected randomized controlled trials (RCTs) for each treatment (tapentadol ER and oxycodone/naloxone ER). As measure of treatment effect, risk ratio was calculated, compared to the control active treatment (CR oxycodone), for the following outcomes: discontinuation rate due to adverse events, due to gastrointestinal (GE) side effects and central nervous system (CNS) side effects. A Markov model was developed to compare the cost effectiveness of tapentadol ER and oxycodone/naloxone ER. Four health states were defined: (1) patients still on treatment; (2) occurrence of adverse events (gastroenterology, central nervous system); (3) treatment discontinuation as consequence of ineffectiveness of treatment; and (4) treatment discontinuation as consequence of adverse events. Results: Both drugs showed a significant clinical advantage over the active control, CR oxycodone; however, tapentadol ER resulted in a better risk ratio reduction for the primary outcome of discontinuation rate due to adverse events and for the secondary outcome nausea and vomiting. The two drugs gave equivalent results in the capacity of reduction of constipation risk. In the economic evaluation both interventions were cost effective compared with CR oxycodone. However, tapentadol ER showed the most favorable results as in 65% of cases it was less costly and produced a considerable quality adjusted life years (QALY) gain. The higher impact of tapentadol ER on the cost effectiveness results was probably due to the price and the lower incidence of adverse events and related discontinuation rate, resulting in a further economic advantage. Conclusion: Both tapentadol ER and oxycodone/naloxone ER are cost effective interventions compared with CR oxycodone; however, tapentadol ER was shown to provide better clinical outcomes at lower costs.